Physical activity and activity space in patients with pulmonary fibrosis not prescribed supplemental oxygen. Issue 1 (December 2017) - Root, Elisabeth; Graney, Bridget; Baird, Susan; Churney, Tara; Fier, Kailtin; Korn, Majorie; McCormic, Mark; Sprunger, David; Vierzba, Tomas; Wamboldt, Frederick; Swigris, Jeffery
Abstract Background Patients with pulmonary fibrosis (PF) have impaired quality of life, and research suggests that dyspnea and physical activity are primary drivers. As PF progresses, some patients notice the disease "shrinks their worlds". The objective of this study is to describe movement (both physical activity and activity space) in a cohort of patients with PF of various etiologies who have not been prescribed supplemental oxygen (O2 ). Methods Subjects with PF not on supplemental O2 during the day were enrolled from across the U.S. from August 2013 to October 2015. At enrollment, each subject completed questionnaires and, for seven consecutive days, wore an accelerometer and GPS tracker. Results One hundred ninety-four subjects had a confirmed diagnosis of PF and complete, analyzable GPS data. The cohort was predominantly male (56%), Caucasian (95%) and had idiopathic pulmonary fibrosis (30%) or connective tissue disease related-PF (31%). Subjects walked a median 7497 (interquartile range [IQR] 5766-9261) steps per day. Steps per day were correlated with symptoms and several quality of life domains. In a model controlling for age, body mass index, wrist- (vs. waist) worn accelerometer and percent predicted diffusing capacity (DLCO%), fatigue (beta coefficient = −51.5 ± 11.7, p < 0.0001) was an independent predictor of steps per day (model R2 =0.34). Conclusions Patients with PF, who have not been prescribed O2 for use during the day, have wide variability in their mobility. Day-to-day physical activity is related to several domains that impact quality of life, but GPS-derived activity space is not. Wearable data collection devices may be used to determine whether and how therapeutic interventions impact movement in PF patients. Trial registration NCT01961362 . Registered 9 October, 2013.